2014
DOI: 10.1177/0269216314551378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a clinical pathway on end-of-life care following stroke: A mixed methods study

Abstract: Distressing stroke-related clinical problems dominated relatives' concerns rather than use of the end-of-life care pathway. At times, relatives felt primarily responsible for key aspects of decision-making. Relatives often felt unprepared for a prolonged dying process after stroke, particularly where patients had persistent major swallowing difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The treating physician carries the final responsibility for medical treatment decisions in incapacitated patients. It can be an enormous emotional burden for legal representatives to feel the sole responsibility for treatment restrictions and it is therefore essential to avoid giving families the impression they are being asked to make these major decisions on their own [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treating physician carries the final responsibility for medical treatment decisions in incapacitated patients. It can be an enormous emotional burden for legal representatives to feel the sole responsibility for treatment restrictions and it is therefore essential to avoid giving families the impression they are being asked to make these major decisions on their own [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a broad consensus that there is an enormous but still underestimated need for palliative care in dying stroke patients [ 13 15 ]. Whereas end-of-life care is well established in diseases such as cancer or advanced heart disease, research on end-of-life care has been relatively neglected in stroke populations and evaluation of end-of-life care processes in stroke has to date been very limited [ 16 18 ]. Moreover, the palliative care needs of acute stroke patients may be very different from those in advanced stages of other chronic diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 In stroke, bereaved relatives reported that while staff discussed with them the likelihood of early death after stroke, they were unprepared for a prolonged dying process. 13 In our study, some professionals said they felt that patients and families did not like being told that the future was uncertain, and this appeared to stop them talking about prognostic uncertainty effectively.…”
Section: Strengths and Weaknesses/limitations Of The Studymentioning
confidence: 76%
“…Two recent studies have explored the views and experiences of patients and carers in some depth. 13,19 We attempted to optimise response rates by ensuring that the survey was short, indicating in a covering email the likely time required for completion, embedding the survey link in the email and sending an email reminder after 2 weeks. 20 Survey Monkey automatically anonymised the data and provided the number of responses in each category.…”
Section: Methodsmentioning
confidence: 99%